Labelling via [Al18F]2+ Using Precomplexed Al-NODA Moieties - Daniel Kang; Ulrich Simon; Felix M. Mottaghy; Andreas T. J. Vogg (Pharmaceuticals, 2021)
Over the past 20 years, 68Ga-labelled radiopharmaceuticals have become an important part in clinical routine. However, the worldwide supply with 68Ge/68Ga generators is limited as well as the number of patient doses per batch of 68Ga radiopharmaceutical. In the recent years, a new technique appeared, making use of the ease of aqueous labelling via chelators as with 68Ga but using 18F instead. This technique takes advantage of the strong coordinative bond between aluminium and fluoride, realized in the aqueous cation [Al18F]2+. Most applications to date make use of one-pot syntheses with free Al(III) ions in the system. In contrast, we investigated the labelling approach split into two steps: generating the Al-bearing precursor in pure form and using this Al compound as a precursor in the labelling step with aqueous [18F]fluoride. Hence, no free Al3+ ions are present in the labelling step. We investigated the impact of parameters: temperature, pH, addition of organic solvent, and reaction time using the model chelator NH2-MPAA-NODA. With optimized parameters we could stably achieve a 80% radiochemical yield exerting a 30-min reaction time at 100 °C. This technique has the potential to become an important approach in radiopharmaceutical syntheses.